Effect of bambara bean and barley flour inclusion on nutritional, functional, structural and pasting properties of broken rice-based blends - Setiyoko, Agus; Sulaiman, Rabiha; Mustapha, Nor Afizah; Ariffin, Mohd Khairol Anuar Mohd; Budijanto, Slamet; Palupi, Eny (Agriculture and Natural Resources, 2026)
Importance of the work: A novel triple-flour blend was developed by mixing underutilized broken rice with barley and bambara bean flour a combination remains to be studied, with other published research focusing mainly on each component individually. Objectives: To investigate the nutritional composition, structural properties, pasting characteristics and functional properties of composite flours. Materials and Methods: Composite flours with varying ratios of broken rice, barley and bambara bean were analyzed for proximate composition, antioxidant activity, functional properties, pasting behavior, Fourier-transform infrared (FTIR) spectra and X-ray diffraction patterns. Results: Increasing the bambara bean flour content significantly enhanced the protein, fiber, fat and antioxidant levels, while reducing the starch and amylose contents. The water absorption index increased with higher inclusion of bambara beans and barley. All blends exhibited A-type crystallinity; however, crystallinity decreased in the high-bambara formulations, indicating an increase in amorphous structures. Reduced setback viscosity was suggested to improve thermal stability and resistance to retrogradation. FTIR spectroscopy confirmed the presence of similar functional groups, with intensity differences reflecting compositional variation. Antioxidant activity increased significantly in the bambara-rich blends. Main finding: These blends offer enhanced nutritional value, functional quality and structural characteristics, highlighting their potential for functional and sustainable food applications.